Transcriptome Analysis and CFEM Gene Overexpression in Metschnikowia bicuspidata Under Hemocyte and Iron Ion Stress - Bingnan Zuo; Xiaodong Li; Ji Zhang; Bingyu Li; Na Sun; Fang Liang (Pathogens, 2025)
The “milky disease” in Chinese mitten crabs (Eriocheir sinensis), caused by Metschnikowia bicuspidata, poses significant threats to aquaculture, though its pathogenic mechanisms remain poorly understood. This study employs transcriptomic sequencing to analyze gene expression changes in Metschnikowia bicuspidata under hemocyte challenge, iron overload (1 mmol/mL), and combined stress, with functional validation through Common in Fungal Extracellular Membrane (CFEMgene) overexpression strains. Key findings reveal that (1) hemocyte challenge activated base excision repair (−log10[P] = 7.58) and ribosome biogenesis pathways, indicating fungal adaptation through DNA repair and enhanced protein synthesis to counter host immune attacks (e.g., ROS-mediated damage). (2) Iron overload induced glutathione metabolism and pentose phosphate pathway enrichment, demonstrating mitigation of ferroptosis through NADPH/GSH antioxidant systems and autophagy/proteasome coordination. (3) Under combined stress, ribosome biogenesis (−log10[P] = 1.3) and non-homologous end-joining pathways coordinated DNA repair with stress protein synthesis, complemented by vacuolar V-ATPase-mediated iron compartmentalization. (4) CFEM genes showed significant upregulation under hemocyte stress, with overexpression strains exhibiting enhanced biofilm formation (35% increased MTT cytotoxicity) and infectivity (40% higher infection rate), confirming CFEM domains mediate pathogenesis through iron homeostasis and virulence factor production. This work elucidates how M. bicuspidata employs metabolic reprogramming, oxidative stress responses, and CFEM-mediated iron regulation to establish infection, providing critical insights for developing targeted control strategies against milky disease.